PENGARUH DPK DAN PEMBIAYAAN TERHADAP PENINGKATAN FEE BASED INCOME PT. BANK SYARIAH MANDIRI - Ismaulina Ismaulina; Nurul Haqiqi (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2018)
Banks obtain funding sources from collecting public funds in the form of demand deposits, savings and time deposits. This funding source is known as third party funds (DPK). Furthermore, the funds are channeled through financing as a banking investment in order to obtain profits from planting or capital participation in businesses run by business people. Financing provided is subject to loan services in the form of administrative fees contained in Fee Based Income. Fee Based Income is the bank's income from services provided. The purpose of this study is to find out why DPK and financing affect the increase in Fee Based Income (FBI). This type of research is quantitative research, using secondary data monthly reports on deposits and financing funds totaling 36 observational data. Data is analyzed by multiple linear regression analysis with the help of EVIEW 10. With a significance level of 0.05 (5%). This happens because the total administration DPK received by Bank Syariah Mandiri is very small or even nonexistent so it does not make a meaningful contribution to the bank's profitability. While the financing variable has an effect on and is significant to the increase in the FBI variable. This happens because the monthly income from the administration of financing has increased, so that with the increase in bank income from this financing, the increase in the total FBI will increase in the bank, so that bank profits will also increase. Keywords : Third Party Funds (DPK), Financing, Fee Based Income (FBI)